Analysis Principles Of Criminal Law In Article 72 Qanun Of Aceh No. 6 Of 2014 On The Jinayat Law - Dhanar Dhono Vernandhie; Sri Kusriyah Kusriyah (Jurnal Daulat Hukum, 2019)
This study describes the applicability of Qanun of Aceh No. 6 of 2014 on the Jinayat law (Qanun of Jinayat) in the order of legislation in Indonesia. Therefore this study to analyze these issues, to examine the legality principle as stated in Article 72 of the Qanun of Jinayat and the rule of law by applying the Qanun of Jinayat. This study uses normative research approach, by analyzing the legal ingredients of primary legal materials, secondary and tertiary. The results and discussion of the research was that Qanun of Jinayat not contrary to the order of Indonesian legislation, both formal legislative process and substantive elements of the rule of law which includes setting legal subjects, actions and sanctions of criminalization. Applicability of Qanun of Jinayat also related to three factors, namely philosophical which is a reflection of the values of the people of Aceh, sociological factors are the result of legal politics of the Government of the Republic of Indonesia and the Free Aceh Movement and the factors juridical is the order of the constitution and legislation that higher. Qanun of Jinayat law enforcement requires the law enforcement agencies, particularly the police for continued and consistent enforcement in order to create legal certainty. Suggestions can be submitted is law enforcement-led policy-making and increased synergies between law enforcement agencies in law enforcement for action based on Qanun of Jinayat Jarimah regulated in Qanun of Jinayat.Keywords: Qanun of Jinayat in Aceh; Legality; Legislation; Law Enforcement.